(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The article presents the problems associated with the pathology of periodontal tissue and conducted its own study using phytopreparations Hemostat gel and Clove essential oil [1-3]. It was found that the traditional approach to the treatment of chronic generalized severe periodontitis has significant drawbacks - the worst indicators of antiinflammatory and reparative activity, a higher percentage of complications compared with phytopreparations, it was also found that the results of the analysis of anti-inflammatory activity based on a decrease in the level of neutrophil infiltration showed that phytopreparations of oral antiseptics have better effectiveness in comparison with synthetic ones [4-6].